Upaya Penanaman Nilai Moderasi Beragama pada Siswa SDN 105337 Pantai Labu Pekan - Siregar, Yusra Dewi; Rambe, Yusuf Hamdani; Siregar, Salsabila Syfa; Simbolon, Sulistina Ratulani; Siregar, Intan Nuriatama (MODELING: Jurnal Program Studi PGMI, 2023)
Indonesia is a country with various tribes, cultures and ethnicities among its people. Indonesia is also one of the countries with the largest population in the world, home to more than 250 million people. With the large number of people in Indonesia there are also many differences in ethnicity, culture and language. Therefore, it is important to instill the values ​​of religious moderation starting from an early age so that children are accustomed to existing differences and are able to understand any differences that exist. The aim of writing this journal is to find out what efforts are made to instill the values ​​of religious moderation in elementary school children, specifically at SDN 105337 Pantai Labu Pekan. The research method is descriptive qualitative because it is in accordance with the problems raised and the subject matter of this research, namely to find out what and how efforts are made to instill the values ​​of religious moderation in children, so data is needed to be described in detail and in depth and as it is. . The data collection technique is observation, interviews and documentation.